Pengaruh Berkumur Larutan Lidah Buaya (Aloe barbadensis) 25% Terhadap Perubahan Skor Debris Index(DI) - Rizki Sofian; Denden Ridwan (Jurnal Kesehatan Gigi (Dental Health Journal), 2026)
Â Oral and dental health is a crucial factor in determining overall systemic health, yet it is often neglected. Debris accumulation is a primary etiological factor for various oral health issues, including gingivitis and dental caries. While mechanical tooth brushing is effective, it has limitations in reaching certain anatomical areas, necessitating complementary interventions such as mouthwash. Objective: This study aimed to analyze the effect of rinsing with a 25% Aloe vera solution on changes in the Debris Index (DI) scores among students at SMP Mutiara 5 Lembang. Methods: The research employed a quasi-experimental method with a pretest-posttest control group design. A total of 44 students were purposively sampled and divided into two groups: an intervention group using a 25% Aloe vera solution and a control group using mineral water. Debris Index (DI) scores were measured on six index teeth. Data analysis was performed using univariate and bivariate (Wilcoxon and mann whitney tests). Results: In the intervention group, the average Debris Index score decreased significantly from 2.3 to 0.9 (p = 0.000). In contrast, the control group showed a non-significant decrease from 2.1 to 1.9 (p = 0.145). The bivariate analysis confirmed that the 25% Aloe vera solution was significantly more effective in lowering debris scores compared to mineral water (p = 0.000). Conclusion: Rinsing with a 25% Aloe vera solution is effective in reducing Debris Index (DI) scores. The natural active compounds in Aloe vera, such as saponins, acemannan, and anthraquinones, work synergistically as natural cleansers and antibacterial agents to improve oral hygiene.